A conceptual design of technical losses assessment and monitoring system for power distribution network in Universiti Teknikal Malaysia Melaka (UTeM) - Ibrahim K.A.; Gan C.K.; Abidin Z.Z.; Au M.T.; Salim N.; Azmi A.N. (Engineering and Scientific Research Groups, 2023)
Conceptual design; Electric network analysis; Energy dissipation; Energy efficiency; Assessment and monitoring; Data requirements; Electricity bill; Higher learning institutions; New facilities; Power distribution network; Proper design; Technical loss; Monitoring